INHIBITION OF PRC2 SUBUNITS TO TREAT EYE DISORDERS - MBEFO, Kamdem Martial; ARSENIJEVIC, Yvan (2021)
The present disclosure provides inhibitors of one or more subunits of polycomb repressive complex 2 (PRC2) for use in the prevention or the treatment of an eye disorder in a subject in need thereof and methods for treating an eye disorder, e.g. non-cancer disorders, in a subject using a therapeutically effective amount of one or more inhibitors of a subunit of polycomb repressive complex 2 (PRC2).In certain embodiments of the methods of the disclosure, the eye disorders are characterized by degeneration or cell death of retinal neurons.In certain embodiments of the methods of the disclosure, the subunit of PRC2 is EZH1 or EZH2, and the inhibitor is an inhibitor of H3K27 trimethylation.